Dual feedback IRC ring for chaotic waveform generation - Manoj Joshi; Ashish Ranjan (IET Circuits, Devices and Systems, 2021)
Abstract The authors have proposed an inverter resistor capacitor (IRC)‐based simple chaotic ring oscillator with dual feedback for the generation of the chaotic waveform. The proposed chaotic system uses three coupled autonomous first‐order differential equations and it can be electrically demonstrated using the complementary metal oxide semiconductor (CMOS) inverters with few passive RC elements for the generation of the high‐frequency strange attractor. The basic dynamical characteristics and multistability property with complex bifurcation pattern in a wide range of parameters are well observed through theoretical as well as numerical simulation analysis using scaled inverse tangent function. In addition, a simple IRC chaotic model design is investigated using 0.18μm MOS transistor parameters with grounded capacitors and an equivalent CMOS‐based scaled inverse tangent function. Moreover, the Cadence post layout simulation gives useful information about the circuit sustainability for IC design with high frequency (MHz), low power dissipation (940 μW) and small chip area (826.3 μm2).